(untitled) (Studia theodisca, 2025)
In his adaptation of J. M. R. Lenz’s Der Hofmeister oder Vorteile der Privaterziehung [The Tutor or The Benefits of a Private Education], Bertolt Brecht foregrounds the theme of what Marx and Engels, among others, defined as ‘German misery’. This study asks how he succeeds in capturing such a complex phenomenon on stage. It argues that Brecht does so by personifying its facets through key characters: Läuffer, the eternal lackey; Pätus, the philistine; and Wenzeslaus, the teacher of the ‘Untertanen’ [the subordinates]. Their interactions reveal German misery as a pervasive social condition cutting across class boundaries.